A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain - Gilgado, José D.; Ledesma, Enrique; Enghoff, Henrik; Mauriès, Jean-Paul; Ortuño, Vicente M. (Zootaxa, 2017)
The chordeumatidan fauna of the Iberian Peninsula is far from being well known, but recent efforts are improving that knowledge. Samplings carried out in the Milieu Souterrain Superficiel (also known as the Mesovoid Shallow Substratum) on several screes of the Sierra de Guadarrama National Park (central Spain) have led to the discovery of a new species of chordeumatidan millipede. This new species belongs to the family Haplobainosomatidae, which is mainly known from the northern Iberian Peninsula, and thus this is the first record of the family in central Spain. However, the extremely simple gonopods of this species are so different from all other known species of the family that it must be placed in a new genus. In this work, a complete description of the species, named as Guadarramasoma ramosae gen. & sp. nov., with a detailed iconography based on scanning electron microscopy images is provided together with a distribution map and a brief discussion of the implications of this new finding.